1997
DOI: 10.1046/j.1365-2141.1997.1222936.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Coagulation Factors, Inhibitors and Activation Markers: The Third Glasgow Monica Survey I. Illustrative Reference Ranges by Age, Sex and Hormone Use

Abstract: Summary. Coagulation factor activity (fibrinogen, VII, VIII and IX), coagulation inhibitor activity (antithrombin, protein C, protein S), and coagulation activation markers (prothrombin fragment F1, 2; thrombin-antithrombin complexes) were measured in 747 men and 817 women aged 25-74 years, randomly sampled from the north Glasgow population in the Third MONICA Survey. Significant effects of age, sex, menopause and hormone use were observed and specific reference ranges are presented to illustrate these effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

32
200
4
7

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 271 publications
(243 citation statements)
references
References 46 publications
32
200
4
7
Order By: Relevance
“…Our findings on the mPC levels in the liver (Fig. 1) indicate that the overall agerelated expression pattern of the mPC gene correlates well with the known age-related pattern of circulatory hPC levels in humans (3,4). Both mPC and hPC rapidly increase their expression during the perinatal stage, followed by a general agestable expression pattern.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Our findings on the mPC levels in the liver (Fig. 1) indicate that the overall agerelated expression pattern of the mPC gene correlates well with the known age-related pattern of circulatory hPC levels in humans (3,4). Both mPC and hPC rapidly increase their expression during the perinatal stage, followed by a general agestable expression pattern.…”
Section: Discussionsupporting
confidence: 54%
“…Human PC 1 is an important component of the anticoagulation pathway, while hFIX is a key blood procoagulation factor playing critical roles in blood coagulation (8,9). Epidemiological studies showed that the activity and plasma levels of hFIX increased significantly with advancing age in normal human populations (3,10). In comparison with hFIX, the plasma levels of hPC showed only marginal age-associated changes (3,11).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Factor VII activity was measured using a one-stage clotting assay and rabbit thromboplastin and results were recorded as a percentage of a reference plasma pool (Lowe et al, 1997). The total plasma concentrations of t-PA antigen were determined by an ELISA (Tintelize t-PA, Biopool, Sweden).…”
Section: Plasma Measuresmentioning
confidence: 99%